Estimasi Sumberdaya Skarn Logam Dasar Dengan Metode Geostatistik Ordinary Kriging Blok A Ruwai Kabupaten Lamandau Provinsi Kalimantan Tengah - Riyadi, Hasan; I Wayan Warmada; Anastasia Dewi Titisari; Arifudin Idrus (Retii, 2023)
This research aims to determine the shape of the block model and the distribution of ore deposits and to determine the results of the resource estimation of base metal skarn. Mineral resource estimation reflects the shape and distribution of a mineral deposit so that it can be used as a basis for estimating reserves or mining activities. The data used in this study are the results of exploration drilling, namely collar, assay, survey and lithology. The estimation of base metal skarn resources in this study uses the ordinary kriging method with a block model measuring 10m x 5m x 3m. The results of the estimation of metal skarn resources of Block A Ruwai using the method obtained tonnage for inferred resources of 19,452 tons, indicated 29,542 tons and measured 16,546 tons with an average Pb-Zn content of 10.71%, 10.85% and 11.51%. The estimation results of the ordinary kriging method were compared with the composite data of Pb-Zn content (raw initial data) to determine its accuracy based on cross validation parameters. From the cross validation results, the RMSE (root mean square error) value is 0.40 which is close to 0 (zero), the correlation coefficient (r) is 0.83 and the coefficient of determination (r2) is 0.7 which is close to 1, so the estimation results are considered good enough.